2009
DOI: 10.1042/cs20080390
|View full text |Cite
|
Sign up to set email alerts
|

Role of the renin–angiotensin–aldosterone system and inflammatory processes in the development and progression of diastolic dysfunction

Abstract: Left ventricular diastolic dysfunction represents a frequent clinical condition and is associated with increased cardiovascular morbidity and mortality. Diastolic dysfunction is the most common cause of HF-PSF (heart failure with preserved ejection fraction). Therefore it becomes important to understand the pathophysiological mechanisms underlying diastolic dysfunction, as well as the effective therapeutic strategies able to antagonize its development and progression. Among the complex pathophysiological facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 106 publications
2
86
0
2
Order By: Relevance
“…6 Similarly, the development of LV diastolic dysfunction has been reported in individuals subjected to prolonged physical inactivity, 7,8 thereby suggesting that patients with SCI might be at a higher risk of developing abnormalities in LV function. The aim of this study was to investigate cardiac functional and structural parameters in SCI and able-bodied subjects and evaluate the impact of clinical, hemodynamic, metabolic and inflammatory variables in this regard.…”
Section: Introductionmentioning
confidence: 91%
“…6 Similarly, the development of LV diastolic dysfunction has been reported in individuals subjected to prolonged physical inactivity, 7,8 thereby suggesting that patients with SCI might be at a higher risk of developing abnormalities in LV function. The aim of this study was to investigate cardiac functional and structural parameters in SCI and able-bodied subjects and evaluate the impact of clinical, hemodynamic, metabolic and inflammatory variables in this regard.…”
Section: Introductionmentioning
confidence: 91%
“…[8][9][10][11][12] ACE inhibitors have been shown to be efficacious not only as therapies against hypertension and protection against left ventricular hypertrophy but also in the regulation of the immune system related to distinct diseases, including the T. cruziinduced pathologies. 9,[13][14][15] Their actions are based on the angiotensin II, a key factor in the renin-angiotensin system that plays an essential role in the regulation of blood pressure, and that also interferes in the cardiac inflammatory activity through the activation of the nuclear factor kappaB (NF-κB) and in the production of inflammatory cytokines and chemokines. 16 In the context of the experimental T. cruzi infection, the ACE inhibitor captopril was previously demonstrated to be able to decrease the delayed-type hypersensitivity response against parasite in acute myocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] Indeed, our study shows adrenal gland hypertrophy and an increase of the aldosterone:renin ratio, 13,14 suggesting that sympathetic activation may be involved in the postnephrectomy hypertrophy of the heart and remnant kidney. Although an activation of the renin-aldosterone system has been shown in patients with chronic kidney disease, 8,31 adrenal hypertrophy has been described only in animal studies. 29,32 Further, aging is an unlikely mechanism of development of LVM because echocardiographic studies in the healthy general population have shown that there is no increase of LVM with age after adjusting for body surface area.…”
Section: Discussionmentioning
confidence: 99%